International human rights law in Africa - Viljoen, Frans (Oxford, U.K. : Oxford University Press, 2012)
This book provides a comprehensive and analytical overview of human rights law in Africa. It examines the institutions, norms, and processes for human rights realization provided for under the United Nations system, the African Union, and sub-regional economic communitites in Africa, and explores their relationship with the national legal systems of African states. Since the establishment of the African Union in 2001, there has been a proliferation of regional institutions that are relevant to human rights in Africa. These include the Pan African Parliament, the Peace and Security Council, the.
An introduction to international human rights law -- The role of United Nations organs and agencies in realizing human rights in Africa -- The United Nations treaty-based human rights system and Africa -- The African Union and human rights architecture -- Substantive human rights norms in the African regional system -- The African Commission : introduction and assessment -- The African Commission : protective mandate -- The African Commission : promotional mandate -- The African children's charter and children's rights committee -- The African Court on Human and Peoples' rights -- The realization of human rights in Africa through subregional institutions -- Domestic implementation of international human rights law in African States -- Conclusion.
Includes bibliographical references (pages 573-601) and index.
Print version record.
Keywords: African Court on Human and Peoples' Rights; African Union; African Commission on Human and Peoples' Rights; African Commission on Human and Peoples' Rights; African Court on Human and Peoples' Rights; African Union; Human rights -- Africa; International agencies -- Africa; Organisations internationales -- Afrique; POLITICAL SCIENCE -- Political Freedom & Security -- Human Rights; Human rights; International agencies; Africa; Human rights; African Charter on Human and Peoples' Rights (Banjul, 27 June 1981); African Commission on Human and Peoples' Rights; African Court of Justice and Human Rights; International law and national law; Africa